Ultrasonographic measurement of subarachnoid space and frontal horn width in healthy Iranian infants - SABOURI, Sofia; KHATAMI, Alireza; SHAHNAZI, Makhtoom; TONEKABONI, Seyyed Hassan; MOMENI, Abbas; MEHRAFARIN, Mastooreh (Iranian Journal of Child Neurology, 2011)
Objective ultrasonography is among the most general evaluating methods for central nervous system (CNS) assessment, especially for detecting extra axial collection via anterior fontanel. There are few studies showing values of this technique in normal developing infants for detection of subarachnoid space width. Association between age and sex and cerebrospinal fluid (CSF) spaces are controversial. Therefore, we conducted this study to evaluate the relationship between subarachnoid space and sex and age in Iranian infants. Material & Methods we used ultrasonography with a 7.5MHZ linear probe to evaluate 74 healthy infants who were referred to our departments for other reasons. Sinocortical width (SCW), craniocortical width (CCW), interhemispheric width (IHW) and frontal horn width (FHW) were evaluated. Data was collected and analyzed using STAT 9.1 software. Results Fifty four percent of the patients were male and 45% were female. Mean age of cases was 71 days. Mean SCW was 2.8 ± 1.33 mm (5% and95% were 1.2-5.8). Mean CCW was 2.52±1.37mm (5% and 95% were 1.1 and 5.2mm, respectively) and mean IHW was 4.39±2mm (5% and 95% were 1.7 and 8mm, respectively). Mean FHW was 2.9+/-1.09mm in females and 3.52±1.34mm in males (5% and 95% were 1.4 and 5mm in females & 1.7 and 5.8mm in males, respectively). There was no significant difference in subarachnoid space width between boys and girls except for FHW which was wider in males than females. (P=0.037). All space diameters correlated with age and were wider in older infants. Conclusion Although our sample size was rather small for accurate conclusion, we found a normal range which was wider than western countries but similar studies conducted in China. Delayed maturation of arachnoid villi is one of the most important reasons of subarachnoid space widening in infants younger than one year which seems occur later in Iranian infants. Key words: Ultrasonography;subarachnoid space; infant.